Match performance of elite soccer players in ratio to contextual variables and game structure in the attack and defense phases using InStat Kinematic System. A longitudinal study - Kosta Goranović; Jovica Petković; Marko Joksimović; Dana Badau; Razvan S. Enoiu (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The practical value of using the wearable devices for monitoring running performance and contextual variables is that well-chosen performance indicators can help coaches identify good and bad performances of individuals or teams. The aim of the article was to investigate running trends in the ratio to the structure of the game in the offensive and defensive phases of professional soccer players on home and away pitches in Montenegro in three competitive matches of different seasons. The research included 82 professional soccer players. The first sub-sample included 44 professional soccer players, height 185.89 ± 6.29 cm, mass 81.06 ± 5.47 kg, BMI 23.47 ± 0.96 kg/m2, age 28.86 ± 3.85 years. The second sub-sample includes 38 professional football players, height 181.88 ± 6.35 cm, mass 77.28 ± 6.78 kg, BMI 23.32 ± 1.08 kg/m2, age 29.43 ± 5.68 years old. The InStat kinematic system recorded field players using six cameras placed around the perimeter of the field at a minimum height of 12 m, 25 frames per second. Our study indicated some contrasting findings. Statistically significant differences were obtained in all three years in running performance and contextual variables. Our results indicate a decreasing trend in high speed runs distance both in the attack phase and in the defense phase for both teams. The conclusion of this study provided information on performance in soccer, which could consequently improve the applicability of running performance in training and competitions